Sexual risk behaviors following circumcision among HIV-positive men in Rakai, Uganda. Issue 8 (3rd August 2018) - Kankaka, Edward Nelson; Ssekasanvu, Joseph; Prodger, Jessica; Nabukalu, Dorean; Nakawooya, Hadijja; Ndyanabo, Anthony; Kigozi, Godfrey; Gray, Ronald
ABSTRACT: Objective: To determine whether circumcision of HIV-positive men is associated with increased subsequent sexual risk behaviors which may place their female partners at risk. Methods: Newly circumcised and uncircumcised HIV-positive men in the Rakai Community Cohort Study were followed from baseline (July 2013–January 2015) to determine trend in sexual risk behaviors and association of circumcision with subsequent sexual risk behaviors at follow up (February 2015–September 2016). Risk behaviors included sexual activity, alcohol before sex, transactional sex, multiple sex partners, casual sex partners, and inconsistent condom use with casual partners. The association was evaluated using modified Poisson regression, and sensitivity analyses were performed after multiple imputation with chained equations for missing data. Results: We identified 538 eligible men, of whom 113(21.0%) were circumcised at baseline and 425(79.0%) were uncircumcised. Men in fishing communities were more likely to be circumcised ( p  = 0.032) as well as those exposed to targeted HIV messaging ( p  < 0.001). Overall, 188(34.9%) men were lost to follow up and most were uncircumcised ( p  = 0.020). Among those followed up, behaviors remained largely unchanged with no differences by circumcision status. Transactional sex appeared to be associated with circumcision in unadjusted analyses (PR = 1.58, 95%CI = 1.01, 2.48; p  = 0.045, p  = 0.05) and adjusted analyses (adj.PR = 1.54, 95%CI = 1.06, 2.23; p  = 0.022). However, the association was no longer significant in sensitivity analyses after accounting for loss to follow up (adj.PR = 1.43, 95%CI = 0.98, 2.08; p  = 0.066). No association with circumcision was observed for other sexual risk behaviors. Conclusion: We found no association between circumcision of HIV-positive men and subsequent sexual risk behavior.